Risk potential of bottom sediments affected by mining tailings from the Fundão dam/ Brazil (Research, Society and Development, 2020)
In 2015, the Gualaxo do Norte river basin suffered from a serious environmental disaster that affected the quality of the river environment due to the disruption of the Fundão dam structures located in the Bento Rodrigues sub-district, Mariana, Minas Gerais/ Brazil. Bottom sediments were one of the environmental matrices most affected by the disaster. In order to assess the risk potential of these matrices and the ecological risk of the aforementioned river, samples were collected from four sample stations on the stretch upstream and downstream of the environmental disaster. These samples were analyzed according to procedure BCR 701, obtaining metals in the exchangeable, reducible, oxidizable and residual fractions. In the exchangeable phase in which metals and semimetals are potentially available to aquatic organisms, concentrations of barium, copper, iron, manganese and zinc were measured, showing a percentage in all sampling stations ranging from 3.7-61.0%, 6.1 -10.8%, 0.2-7.6%, 1.6-23.1%, and 4.1-16.7%. Regarding the potential for ecological risk, there was a greater ecological risk in the stations affected by the iron ore tailings from the dam. Barium concentrations presented medium to extremely high risk at the sampling stations analyzed. This result possibly indicates that its concentrations in the Gualaxo do Norte River may cause harmful effects to aquatic biota.